Asymmetric degradable fluorenyl polymer as well as synthesis method and application thereof

Through efficient selective separation technology of asymmetric degradable fluorenyl polymers and single-wall carbon nanotubes, the problem of residual polymers on the surface of carbon nanotubes damage electronic devices is solved, and the separation and clean release of high-purity carbon nanotubes are achieved. .

CN119306907APending Publication Date: 2025-01-14SHANXI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411373130.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The remaining polymers on the surface of carbon nanotubes impair electronic device performance, especially in the high purity separation and application of semiconductor single-wall carbon nanotubes.

Method used

Using an asymmetrically degradable fluorenyl polymer, the polymer is prepared by a specific synthetic method, and the polymer and carbon are achieved by efficient selective separation from single-walled carbon nanotubes combined with ultrasonic and centrifugal technology. The stable dispersion and separation of nanotubes followed by effective removal of polymer under the action of trifluoroacetic acid.

Benefits of technology

Separation and sorting of semiconductor single-walled carbon nanotubes with high purity (>99.9%) was achieved, reducing the damage to the performance of the carbon nanotubes by polymers, and ensuring the clean release of the carbon tubes through degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306907A_ABST
    Figure CN119306907A_ABST
Patent Text Reader

Abstract

The invention discloses an asymmetric degradable fluorenyl polymer as well as a synthesis method and application thereof, and belongs to the technical field of carbon nanotube separation. Aiming at the problem that an electronic device is damaged by a polymer remaining on the surface of a current carbon nanotube, the invention designs an asymmetric polymer containing an imine bond by separating the single-walled carbon nanotube through a polymer wrapping method, and achieves the efficient separation of the semiconductor type single-walled carbon nanotube by changing the charge property of the polymer. The synthesis method is single, the cost is lower, the yield is higher, the operation is simple and efficient, the semiconductor type single-walled carbon nanotubes with the purity exceeding 99.9% can be effectively separated from the synthesized polymer, and due to the degradability of the polymer, the polymer wrapping the carbon tubes can be effectively removed under the stimulation of trifluoroacetic acid, so that the clean carbon tubes are released.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon nanotube separation, and in particular relates to an asymmetric degradable fluorene-based polymer and a synthesis method and application thereof. Background Art

[0002] Since the discovery of carbon nanotubes by Lijima in 1991, their excellent electrical, optical, mechanical and thermal properties have quickly become one of the research hotspots in the fields of physics, chemistry, and materials science. Single-walled carbon nanotubes can be divided into metallic single-walled carbon nanotubes (m-SWCNTs) and semiconducting single-walled carbon nanotubes (s-SWCNTs).

[0003] Semiconducting single-walled carbon nanotubes (s-SWCNTs) have higher mobility than traditional semiconductors and have broad prospects from field-effect transistors to printed thin-film transistors. High-end electronic device applications require single-walled carbon nanotubes with a semiconducting purity of >99.9999%, so it is crucial to separate pure s-SWCNTs from the original SWCNTs mixture.

[0004] The polymer wrapping method has attracted widespread attention due to its simple operation process and high purification efficiency. However, the residual polymer on the surface of carbon nanotubes will damage the performance of electronic devices in practical applications. Summary of the invention

[0005] In view of the problem that the polymer remaining on the surface of carbon nanotubes damages electronic devices, the present invention provides an asymmetric degradable fluorene-based polymer and a synthesis method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: An asymmetric degradable fluorene-based polymer, the general structural formula of the fluorene-based polymer is: ; The fluorene-based polymer specifically includes: fluorene-based polymer P1, fluorene-based polymer P2 and fluorene-based polymer P3; Ar1 in fluorene polymer P1 = ;Ar2= ; ; Ar1 in fluorene polymer P2 = ;Ar2= ; ; Ar1 in fluorene polymer P3 = ;Ar2= ; .

[0007] Furthermore, the synthesis method of the fluorene-based polymer P1 specifically comprises the following steps: Step 1.1, using 2,7-dibromo-9,9-docosylfluorene and 4-formylphenylboronic acid as raw materials, adding a solvent and mixing them, and reacting them under the catalysis of tetrakistriphenylphosphine palladium to synthesize 4-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)benzaldehyde; Step 1.2, 4-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)benzaldehyde and 6-aminopyridine boronic acid are used as raw materials, a solvent is added and mixed, and a coupling reaction is carried out under the catalysis of tetrakistriphenylphosphine palladium to synthesize an asymmetric fluorene-based polymer P1.

[0008] Furthermore, both step 1.1 and step 1.2 are carried out under a nitrogen atmosphere; after the reaction of step 1.1 and step 1.2 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator; Furthermore, the substances after the reaction in step 1.1 and step 1.2 are purified by silica gel column chromatography; the purified substance in step 1.2 is dissolved in toluene, and then cold methanol solvent is added dropwise, and the precipitate is collected; methanol is then used for Soxhlet purification; the volume ratio of toluene to cold methanol is 1:50; the temperature for Soxhlet purification is 130° C., and the purification time is 24 hours; Furthermore, in the step 1.1, the molar mass ratio of 2,7-dibromo-9,9-docosylfluorene to 4-formylphenylboronic acid is 1:1.2~2; in the step 1.2, the molar mass ratio of 4-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)benzaldehyde to 6-aminopyridineboronic acid is 1:1.2~2; the solvent is toluene and potassium carbonate aqueous solution in a volume ratio of 4~5:1; Furthermore, the reaction temperature in step 1.1 and step 1.2 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

[0009] Furthermore, the synthesis method of the fluorene-based polymer P2 specifically comprises the following steps: Step 2.1, using 2,7-dibromo-9,9-docosylfluorene and 5-formyl-2-thiopheneboronic acid as raw materials, adding a solvent and mixing them evenly, coupling them under the catalysis of tetrakistriphenylphosphine palladium to synthesize 5-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde; Step 2.2, 5-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde and 4-aminophenylboronic acid pinacol ester are mixed as raw materials with a solvent, and coupled under the catalysis of tetrakistriphenylphosphine palladium to synthesize an asymmetric fluorenyl polymer P2.

[0010] Furthermore, after the reaction of step 2.1 and step 2.2 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried over anhydrous magnesium sulfate, and the solvent is removed using a rotary evaporator; Furthermore, the substances after the reaction in step 2.1 and step 2.2 are purified by silica gel column chromatography; Further, the purified substance in step 2.2 is dissolved in toluene, and then cold methanol solvent is added dropwise to collect the precipitate; methanol is then used for Soxhlet purification; the volume ratio of toluene to cold methanol is 1:50; the temperature for Soxhlet purification is 130° C., and the purification time is 24 hours; Furthermore, in the step 2.1, the molar mass ratio of 2,7-dibromo-9,9-dodecylfluorene to 5-formyl-2-thiopheneboronic acid is 1:1.2~2; in the step 2.2, the molar mass ratio of 5-(7-bromo-9,9-dodecyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde to 4-aminophenylboronic acid pinacol ester is 1:1.2~2; the solvent is toluene and potassium carbonate aqueous solution in a volume ratio of 4~5:1; Furthermore, the reaction temperature in step 2.1 is 60°C to 110°C, and the reaction time is 8h to 24h; Furthermore, the reaction temperature in step 2.2 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

[0011] Furthermore, the synthesis method of the fluorene-based polymer P3 specifically includes the following steps: 5-(7-bromo-9,9-dioctyl-9H-fluorene-2-yl)thiophene-2-carboxaldehyde and 6-aminopyridine boronic acid are mixed as raw materials with a solvent, and an asymmetric fluorene-based polymer P3 is synthesized under the catalysis of tetrakistriphenylphosphine palladium.

[0012] Furthermore, after the reaction in step 3.1 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried over anhydrous magnesium sulfate, and the solvent is removed using a rotary evaporator; Furthermore, the substances after the reaction in step 3.1 are purified by silica gel column chromatography; the purified substances are dissolved in toluene, and then cold methanol solvent is added dropwise to collect the precipitate; and then methanol is used for Soxhlet purification; Furthermore, the volume ratio of toluene and cold methanol is 1:50; the temperature of Soxhlet purification is 130°C, and the purification time is 24h; Furthermore, in the step 3.1, the molar mass ratio of 5-(7-bromo-9,9-docosanyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde to 6-aminopyridine boronic acid is 1:1.2~2; the volume ratio of the solvent is toluene and potassium carbonate aqueous solution is 4~5:1; Furthermore, the reaction temperature in step 3.1 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

[0013] An application of an asymmetric degradable fluorene-based polymer synthesized by the above-mentioned synthesis method in the efficient and selective separation of semiconductor single-walled carbon nanotubes comprises the following steps: Step 1, dissolving the polymer in toluene, dissolving the polymer completely by bath sonication, adding single-walled carbon nanotubes (Arc-SWCNTs) prepared by arc method, and performing bath sonication and centrifugation; Step 2, collecting 80% of the supernatant after centrifugation to obtain a stable dispersion of the polymer and the semiconductor single-walled carbon nanotubes, and then performing UV-Vis-NIR spectral testing.

[0014] Furthermore, in step 1, the ratio of the polymer, toluene and single-walled carbon nanotubes is 1 mg: 6 mL: 1 mg; Furthermore, in step 1, the power of the bath ultrasound is 480 W, the treatment time is 10 to 20 min, the temperature is cooled to 10° C., and the ultrasound operation is repeated twice; Furthermore, in step 1, the centrifugal speed is 15300 rpm (centrifugal force: 19800 g), the centrifugal time is 30 min, and the temperature during centrifugation is controlled at 15°C.

[0015] Compared with the prior art, the present invention has the following advantages: The synthesis method of the present invention is simple, low in cost, high in yield, simple and efficient in operation. The polymer synthesized by the present invention can effectively sort out semiconductor single-walled carbon nanotubes with a purity exceeding 99.9%, and due to its degradability, the polymer wrapped on the carbon tube can be effectively removed under the stimulation of trifluoroacetic acid, thereby releasing clean carbon tubes. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 are the UV-visible-near-infrared spectra of polymer P1 and SWCNTs.

[0017] Figure 2 It is the UV-visible-near-infrared spectra of polymer P2 and SWCNTs.

[0018] Figure 3 It is the UV-visible-near-infrared spectra of polymer P3 and SWCNTs.

[0019] Figure 4 The mixture of polymer P1 and SWCNTs was analyzed by Raman spectroscopy at 785 nm laser.

[0020] Figure 5The mixture of polymer P2 and SWCNTs was analyzed by Raman spectroscopy at 785 nm laser.

[0021] Figure 6 The mixture of polymer P3 and SWCNTs was analyzed by Raman spectroscopy at 785 nm laser.

[0022] Figure 7 This is the UV spectrum of polymer P1 before and after adding trifluoroacetic acid.

[0023] Figure 8 This is the UV spectrum of polymer P2 before and after adding trifluoroacetic acid.

[0024] Fig. 9 This is the UV spectrum of polymer P3 before and after adding trifluoroacetic acid.

[0025] Fig.10 This is the X-ray photoelectron spectrum of the polymer-separated carbon tubes before and after adding trifluoroacetic acid. DETAILED DESCRIPTION

[0026] In order to gain a deeper understanding of the present invention, we will provide a comprehensive and detailed description of the present invention. However, the present invention has multiple implementations and is not limited to the specific examples listed herein. The presentation of these examples is intended to deepen the comprehensive understanding of the disclosure of the present invention.

[0027] Example 1

[0028] An asymmetrically synthesized polymer in this embodiment has the structural formula:

[0029] The synthesis method is: Under nitrogen atmosphere, 2,7-dibromo-9,9-dodecylfluorene (1.0 g, 1.51 mmol) and 4-formylphenylboronic acid (0.27 g, 1.81 mmol) were added to a three-necked flask containing 20 mL of toluene.

[0030] Aqueous potassium carbonate (5 mL, 2 M) solution and tetrakis(triphenylphosphine)palladium (0.05 g, 0.045 mmol) were added, and the mixture was stirred at 110° C. for 48 h under nitrogen protection.

[0031] After the reaction was completed, the mixture was cooled to room temperature, extracted with dichloromethane and washed with water. The combined organic phases were dried over anhydrous magnesium sulfate and the solvent was removed using a rotary evaporator.

[0032] The crude product was purified by silica gel column chromatography (petroleum ether:ethyl acetate 20:1) to obtain 0.43 g of bright yellow oil (4-(7-bromo-9,9-docosanyl-9H-fluoren-2-yl)benzaldehyde) with a yield of 41%.

[0033] The molecular formula is C 44 H 61 B O H NMR characterization: 1 H NMR (600 MHz, CDCl3) δ 10.08 (s, 1H), 7.98 (d, J = 8.2Hz, 2H), 7.82 (d, J = 8.0 Hz, 2H), 7.76 (d, J = 7.9 Hz, 1H), 7.65 – 7.55 (m,3H), 7.49 (s, 2H), 1.99 (d, J = 14.7 Hz, 4H), 1.13 (d, J = 85.3 Hz, 36H), 0.86 (t, J = 7.1 Hz, 6H), 0.64 (s, 4H).

[0034] Under nitrogen atmosphere, 4-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)benzaldehyde (0.2 g, 0.3 mmol) and 6-aminopyridine boronic acid (0.08 g, 0.6 mmol) were added to a three-necked flask containing 20 mL of toluene.

[0035] 4 mL of potassium carbonate (2 M) aqueous solution and tetrakis(triphenylphosphine)palladium (0.06 g, 0.05 mmol) were added, and the mixture was stirred at 105° C. under nitrogen protection for 36 hours.

[0036] After cooling to room temperature, the reaction mixture was extracted with dichloromethane and washed with water. The combined organic phases were dried over anhydrous magnesium sulfate and the solvent was removed using a rotary evaporator. The crude product was purified by column chromatography (petroleum ether: ethyl acetate 200:1-20:1). The resulting polymer was dissolved in 1 mL of toluene and then slowly added to 50 mL of methanol to obtain a precipitate.

[0037] Further, Soxhlet extraction was performed with methanol solvent at 130 °C for 24 h to obtain 0.14 g of a yellow-green solid (P1) with a yield of 69%.

[0038] H NMR characterization: 1 H NMR (600 MHz, CDCl3) δ 9.93 (s, 0.1H), 8.68 (s, 1H), 7.85 – 7.73 (m, 6H), 7.71 (s, 1H), 7.66 (d, J = 6.4 Hz, 1H), 7.63 (s, 1H), 7.53 (d, J= 16.3 Hz, 1H), 7.48 (s, 1H), 7.43 (s, 2H), 2.07 (s, 4H), 1.57 (s,2H), 1.27 (s, 6H), 1.17 (s, 16H), 1.10 (s, 12H), 0.87 (t, J = 6.6 Hz, 6H),0.74 (s, 4H).

[0039] Gel chromatography characterization: Mn: 8.2 (KDa), Mw: 10.2 (KDa), PDI (Mw / Mn): 1.24.

[0040] Example 2

[0041] An asymmetrically synthesized polymer in this embodiment has the structural formula:

[0042] An asymmetrically synthesized polymer in this embodiment comprises the following steps: Under a nitrogen atmosphere, 2,7-dibromo-9,9-dodecylfluorene (0.6 g, 0.9 mmol) and 5-aldehyde-2-thiopheneboronic acid (0.28 g, 1.8 mmol) were added to a three-necked flask containing 20 mL of toluene.

[0043] Aqueous potassium carbonate (4 mL, 1 M) solution and tetrakis(triphenylphosphine)palladium (0.05 g, 0.045 mmol) were added, and the mixture was stirred at 65° C. for 8 hours under nitrogen protection.

[0044] The reaction mixture was extracted with dichloromethane and washed with water. The combined organic phases were dried over anhydrous magnesium sulfate. The solvent was removed using a rotary evaporator, and the crude product was finally purified by column chromatography (petroleum ether: ethyl acetate 10:1) to obtain a yellow oily substance, which was recrystallized in methanol to obtain a light yellow solid (5-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde) (0.19 g, yield: 30%).

[0045] The molecular formula is C 42 H 59 BrOS H NMR characterization: 1 H NMR (600 MHz, CDCl3) δ 9.91 (s, 1H), 7.76 (d, J = 3.8Hz, 1H), 7.68 (dt, J = 7.9, 4.6 Hz, 2H), 7.61 – 7.56 (m, 2H), 7.48 (dd, J =5.9, 3.5 Hz, 3H), 1.97 (d, J = 8.6 Hz, 4H), 1.25 (s, 6H), 1.21 – 1.12 (m,18H), 1.05 (s, 12H), 0.86 (t, J = 7.1 Hz, 6H), 0.62 (s, 4H).

[0046] Under nitrogen atmosphere, (5-(7-bromo-9,9-docosanyl-9H-fluoren-2-yl)thiophene-2-carbaldehyde) (0.3 g, 0.43 mmol) and 4-aminophenylboronic acid pinacol ester (0.08 g, 0.65 mmol) were added to a three-necked flask containing 20 mL of toluene.

[0047] 5 mL of potassium carbonate (2 M) aqueous solution and 24.8 mg of tetrakis(triphenylphosphine)palladium (0.02 mmol) were added and stirred at 105° C. for 36 hours under nitrogen protection.

[0048] After cooling to room temperature, the reaction mixture was extracted with dichloromethane, washed with water, and the combined organic phases were dried over anhydrous magnesium sulfate.

[0049] The solvent was removed using a rotary evaporator, and the crude sample was eluted on a silica gel column using a mixed solvent of petroleum ether:ethyl acetate (200:1-20:1).

[0050] The polymer was dissolved in 1 mL of toluene and then slowly added to 50 mL of methanol to obtain a precipitate. The precipitate was further extracted with methanol solvent at 130°C for 24 h to obtain 0.21 g of a yellow solid (P2) with a yield of 68%.

[0051] H NMR characterization: 1 H NMR (600 MHz, CDCl3) δ 10.09 (s, 0.1H), 8.85 (s, 1H), 8.12 (d, J = 41.6 Hz, 3H), 7.84 (s, 4H), 7.64 (d, J = 27.1 Hz, 4H), 7.50 (s,1H), 2.10 (s, 4H), 1.63 (s, 8H), 1.18 (dd, J= 60.1, 35.0 Hz, 34H), 0.85 (s, 4H).

[0052] Gel chromatography characterization: Mn: 8.6 (KDa), Mw: 15.2 (KDa), PDI (Mw / Mn): 1.77.

[0053] Example 3

[0054] An asymmetrically synthesized polymer in this embodiment has the structural formula:

[0055] An asymmetrically synthesized polymer in this embodiment comprises the following steps: Under nitrogen atmosphere, (5-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)thiophene-2-carbaldehyde) (0.3 g, 0.43 mmol) and 6-aminopyridine boronic acid (0.07 g, 0.52 mmol) were added to a three-necked flask containing 20 mL of toluene.

[0056] 5 mL of potassium carbonate (2 M) aqueous solution and 24.8 mg of tetrakis(triphenylphosphine)palladium (0.02 mmol) were stirred at 100 °C under nitrogen protection for 24 h.

[0057] After cooling to room temperature, the reaction mixture was extracted with dichloromethane and washed with water. The organic phase was dried over anhydrous magnesium sulfate and the solvent was removed by a rotary evaporator.

[0058] The crude product was purified by column chromatography (petroleum ether: ethyl acetate 400:1-10:1). 1 mL of toluene was used to dissolve the polymer, which was slowly added to 50 mL of methanol solvent for precipitation. Finally, the precipitate was further extracted with methanol at 130 °C for 24 h to obtain 0.17 g of brown solid (P3) with a yield of 57%.

[0059] H NMR characterization: 1 H NMR (600 MHz, CDCl3) δ 9.92 (s, 0.2H), 8.81 (s, 1H), 8.05 (s, 1H), 7.77 (dd, J = 41.7, 25.6 Hz, 5H), 7.62 (d, J = 25.5 Hz, 3H),7.46 (d, J = 36.0 Hz, 2H), 2.06 (s, 4H), 1.17 (dd, J= 62.6, 38.6 Hz, 42H), 0.85 – 0.80 (m, 4H).

[0060] Gel chromatography characterization: Mn: 3.2 (KDa), Mw: 11.3 (KDa), PDI (Mw / Mn): 3.54.

[0061] Test Example 1 Preparation and separation selectivity of Arc-SWCNTs dispersions by the polymers of Examples 1, 2, and 3.

[0062] 1 mg of each polymer of Examples 1, 2, and 3 was selected and dissolved in 6 mL of toluene. The polymer was completely dissolved by bath ultrasound. Then 1 mg of single-walled carbon nanotubes was added and treated by bath ultrasound for 45 min (480 W). The polymer / carbon nanotube mixture was then added to a 10 mL centrifuge tube and centrifuged at 15°C for 30 min at 15300 rpm (centrifugal force: 19800 g). After centrifugation, 80% of the supernatant was collected to obtain a stable dispersion of the polymer and single-walled carbon nanotubes for UV-Vis-NIR spectral testing.

[0063] The dispersion prepared from the polymer and single-walled carbon nanotubes of Examples 1 and 2 was subjected to UV-Vis-NIR spectral testing. The M11 region (600 nm~850 nm) is the absorption peak of the metallic single-walled carbon nanotubes. They are all very smooth and have deep "valleys". The dispersion prepared from the polymer and single-walled carbon nanotubes of Example 3 has two small peaks in the M11 region (600 nm~850 nm). The metallic single-walled carbon nanotubes are obvious in the dispersion. The UV-Vis-NIR spectral test results are shown in Figure 1 , 2, 3.

[0064] Quantitative analysis of the content of metallic single-walled carbon nanotubes in the films prepared from the polymers of Examples 1, 2, and 3 and Arc-SWCNTs.

[0065] The dispersion prepared from the polymer and single-walled carbon nanotubes of Examples 1, 2, and 3 was filtered through a nylon filter membrane with a pore size of 0.22 µm, and then washed repeatedly with 10 mL of toluene and 10 mL of tetrahydrofuran solution, respectively, to form a layer of black substance on the filter membrane. The black substance was dissolved in 2 mL of dichloromethane solution, and the dichloromethane solution containing SWCNTs was slowly dripped onto a 1 cm×1 cm silicon wafer and Raman test was performed to quantitatively analyze the content of metallic single-walled carbon nanotubes.

[0066] The polymers of Examples 1 and 2 and the films prepared by Arc-SWCNTs were analyzed by Raman spectroscopy. The peak of the metallic single-walled carbon nanotubes in the RBM region disappeared, while the polymers of Example 3 and the films prepared by Arc-SWCNTs had obvious metallic peaks. Figure 4 , Figure 5 and Figure 6 .

[0067] Test Example 2 Degradation of polymer The polymers of Examples 1, 2, and 3 were prepared into 0.025 mg / mL solutions for UV spectrum testing, 0.3% trifluoroacetic acid (TFA) was added for degradation, and UV spectrum testing was performed again.

[0068] UV spectrum test results are shown in Figure 7 , Figure 8 and Fig. 9 As can be seen from the figure: when TFA is added to the P1 solution, its UV maximum absorption peak moves from 396 nm to the maximum absorption peak of the monomer at 345 nm. When TFA is added to P2, the peak absorption intensity at 535 nm decreases, and the maximum absorption peaks show double peaks at 375 nm and 575 nm. When TFA is added to the P3 solution, its UV maximum absorption peak moves from 440 nm to the maximum absorption peak of the monomer at 345 nm.

[0069] This indicates that under acid stimulation, the polymer imine bonds can be successfully degraded into monomers.

[0070] Test Example 3 Removal of polymer from the carbon tube surface The polymer-wrapped carbon tubes of Example 1 were compared by X-ray photoelectron spectroscopy (XPS) of the polymer-wrapped carbon tubes before and after adding 0.3% trifluoroacetic acid (TFA) to examine the N content in the polymer before and after degradation and verify whether the polymer was completely peeled off from the carbon tubes. The XPS spectrum shows that in the N1 spectrum of the polymer-wrapped carbon tubes, the nitrogen element has an obvious peak, while the peak of the nitrogen element disappears in the carbon tubes after acid stimulation and degradation. This confirms the effective degradation and complete removal of the polymer on the surface of SWCNTs. The X-ray photoelectron spectrum of the test is shown in Fig.10 .

[0071] The contents not described in detail in the specification of the present invention belong to the prior art known to the professional and technical personnel in the field. Although the illustrative specific embodiments of the present invention are described above to facilitate the understanding of the present invention by the technical personnel in the field, it should be clear that the present invention is not limited to the scope of the specific embodiments. For the ordinary technical personnel in the field, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

Claims

1. An asymmetric degradable fluorene-based polymer, characterized in that: The general structural formula of the fluorene-based polymer is: ; The fluorene-based polymer specifically includes: fluorene-based polymer P1, fluorene-based polymer P2 and fluorene-based polymer P3; Ar1 in fluorene polymer P1 = ;Ar2= ; ; Ar1 in fluorene polymer P2 = ;Ar2= ; ; Ar1 in fluorene polymer P3 = ;Ar2= ; 。 2. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 1, characterized in that: The synthesis method of the fluorene-based polymer P1 specifically comprises the following steps: Step 1.1, using 2,7-dibromo-9,9-docosylfluorene and 4-formylphenylboronic acid as raw materials, adding a solvent and mixing them, and reacting them under the catalysis of tetrakistriphenylphosphine palladium to synthesize 4-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)benzaldehyde; Step 1.2, 4-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)benzaldehyde and 6-aminopyridine boronic acid are used as raw materials, a solvent is added and mixed, and a coupling reaction is carried out under the catalysis of tetrakistriphenylphosphine palladium to synthesize an asymmetric fluorene-based polymer P1.

3. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 2, characterized in that: The steps 1.1 and 1.2 are both carried out under a nitrogen atmosphere; After the reaction of step 1.1 and step 1.2 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator; The substances after the reaction in step 1.1 and step 1.2 are purified by silica gel column chromatography; Dissolve the purified substance in step 1.2 in toluene, then drop cold methanol solvent into it, collect the precipitate, and then purify it by Soxhlet treatment with methanol; The volume ratio of toluene to cold methanol is 1:50; the temperature of Soxhlet purification is 130°C and the purification time is 24h; In the step 1.1, the molar mass ratio of 2,7-dibromo-9,9-docosylfluorene to 4-formylphenylboronic acid is 1:1.2-2; in the step 1.2, the molar mass ratio of 4-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)benzaldehyde to 6-aminopyridineboronic acid is 1:1.2-2; the solvent is toluene and potassium carbonate aqueous solution in a volume ratio of 4-5:1; The reaction temperature in step 1.1 and step 1.2 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

4. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 1, characterized in that: The synthesis method of the fluorene-based polymer P2 specifically comprises the following steps: Step 2.1, using 2,7-dibromo-9,9-docosylfluorene and 5-formyl-2-thiopheneboronic acid as raw materials, adding a solvent and mixing them evenly, coupling them under the catalysis of tetrakistriphenylphosphine palladium to synthesize 5-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde; Step 2.2, 5-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde and 4-aminophenylboronic acid pinacol ester are mixed as raw materials with a solvent, and coupled under the catalysis of tetrakistriphenylphosphine palladium to synthesize an asymmetric fluorenyl polymer P2.

5. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 4, characterized in that: After the reaction of step 2.1 and step 2.2 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator; The substances after the reaction in step 2.1 and step 2.2 are purified by silica gel column chromatography; Dissolve the purified substance in step 2.2 in toluene, then drop cold methanol solvent into it, collect the precipitate, and then purify it by Soxhlet treatment with methanol; The volume ratio of toluene to cold methanol is 1:50; the temperature of Soxhlet purification is 130°C and the purification time is 24h; In the step 2.1, the molar mass ratio of 2,7-dibromo-9,9-docosylfluorene to 5-formyl-2-thiopheneboronic acid is 1:1.2-2; in the step 2.2, the molar mass ratio of 5-(7-bromo-9,9-docosyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde to 4-aminophenylboronic acid pinacol ester is 1:1.2-2; the solvent is toluene and potassium carbonate aqueous solution in a volume ratio of 4-5:1; The reaction temperature in step 2.1 is 60°C to 110°C, and the reaction time is 8h to 24h; The reaction temperature in step 2.2 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

6. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 1, characterized in that: The synthesis method of the fluorene-based polymer P3 specifically comprises the following steps: Step 3.1, 5-(7-bromo-9,9-dioctyl-9H-fluoren-2-yl)thiophene-2-carboxaldehyde and 6-aminopyridine boronic acid are used as raw materials and mixed with a solvent, and an asymmetric fluorenyl polymer P3 is synthesized under the catalysis of tetrakistriphenylphosphine palladium.

7. The method for synthesizing an asymmetric degradable fluorene-based polymer according to claim 6, characterized in that: After the reaction in step 3.1 is completed, the mixture is cooled to room temperature, extracted with dichloromethane and washed with water; the combined organic phase is dried with anhydrous magnesium sulfate, and the solvent is removed with a rotary evaporator; The substances after the reaction in step 3.1 are purified by silica gel column chromatography; the purified substances are dissolved in toluene, and then cold methanol solvent is added dropwise to collect the precipitate; and then methanol is used for Soxhlet purification; The volume ratio of toluene to cold methanol is 1:50; the temperature of Soxhlet purification is 130°C and the purification time is 24h; In the step 3.1, the molar mass ratio of 5-(7-bromo-9,9-docosanyl-9H-fluorene-2-yl)thiophene-2-carboxaldehyde to 6-aminopyridine boronic acid is 1:1.2-2; the volume ratio of the solvent is toluene and potassium carbonate aqueous solution is 4-5:1; The reaction temperature in step 3.1 is 100° C. to 110° C., and the reaction time is 24 h to 48 h.

8. Use of an asymmetric degradable fluorene-based polymer synthesized by the synthesis method according to any one of claims 2 to 7 in the efficient and selective separation of semiconducting single-walled carbon nanotubes, characterized in that: The following steps are involved: Step 1, dissolving the polymer in toluene, dissolving the polymer completely by bath sonication, adding the single-walled carbon nanotubes prepared by the arc method, and performing bath sonication and centrifugation; Step 2, collecting 80% of the supernatant after centrifugation to obtain a stable dispersion of the polymer and the semiconductor single-walled carbon nanotubes, and then performing UV-Vis-NIR spectral testing.

9. The use of the asymmetric degradable fluorene-based polymer according to claim 8 in the efficient and selective separation of semiconducting single-walled carbon nanotubes, characterized in that: In the step 1, the ratio of the polymer, toluene and single-walled carbon nanotubes is 1 mg: 6 mL: 1 mg; In step 1, the power of the bath ultrasound is 480W, the treatment time is 10-20min, the temperature is cooled to 10°C, and the ultrasound operation is repeated twice; In step 1, the centrifugal speed is 15300 rpm, the centrifugal time is 30 min, and the temperature during centrifugation is controlled at 15°C.

Citation Information

Cited By

  • Method for preparing single-walled carbon nanotube

    CN120864485A